2001
DOI: 10.3748/wjg.v7.i4.587
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of malignant digestive tract obstruction by combined intraluminal stent installation and intra-arterial drug infusion

Abstract: AIM To study the palliative treatment of malignant obstrution of digestive tract with placement of intraluminal stent combined with intra-arterial infusion of chemotherapeutic drugs.METHODS A total of 281 cases of digestive tract malignant obstruction were given per oral (esophagus, stomach, duodenum and jejunum), per anal (colon and rectum) and percutaneous transhepatic (biliary) installation of metallic stent. Among them, 203 cases received drug infusion by cannulation of tumor supplying artery with Seldinge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Moreover, GPS and KPS scores in various postoperative periods were lower than those in the control group (P < 0.05). our results could comparable to previous studies using other palliative tube decompression percutaneous endoscopic gastrostomy (PEG) [21,40,43] or percutaneous radiologic gastrostomy (PRG) [20,22,38] and intraluminal stent installation [33,36,37,41,42] . This indicates that the combination of ileus tube and arterial infusion chemotherapy can effectively relieve clinical symptoms of malignant small bowel obstruction and signi cantly prolong patient survival time.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, GPS and KPS scores in various postoperative periods were lower than those in the control group (P < 0.05). our results could comparable to previous studies using other palliative tube decompression percutaneous endoscopic gastrostomy (PEG) [21,40,43] or percutaneous radiologic gastrostomy (PRG) [20,22,38] and intraluminal stent installation [33,36,37,41,42] . This indicates that the combination of ileus tube and arterial infusion chemotherapy can effectively relieve clinical symptoms of malignant small bowel obstruction and signi cantly prolong patient survival time.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, these approaches facilitate prompt resumption of oral intake in individuals with malignant intestinal obstruction and can withstand subsequent antitumor therapy [39] . Although, it has been observed that MBO can be effectively addressed through the implementation of both intraluminal stent installation and intra-arterial drug infusion [40][41][42] , nevertheless, this approach is frequently accompanied by complications such as upper gastrointestinal or colon obstruction, and its applicability is restricted to solitary stenosis lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with dolantin was not satisfactory, and venous injection of omeprazole and peridural anesthesia were used for 2 days to relieve the pain. In terms of pain after stent placement, the incidence (16.7%) was slightly higher than those reported previously [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] . This may be attributable to the types of lesions and size of the stents.…”
Section: Discussionmentioning
confidence: 61%
“…After duplicate removal and three-step selection, a total of 40 articles were assessed for eligibility by their full text. Out of these studies, 23 were excluded for the following reasons: lack of intervention group (6 studies, [17][18][19][20][21][22]), lack of a control group (3 studies, [23][24][25]), insufficient outcome data (7 studies, [26][27][28][29][30][31][32]), use of non-metallic stents (2 studies, [33,34]), patients with curable cancer (2 studies, [35,36]) and curative intent (3 studies, [37][38][39]). For a summary of our search and selection, see Fig.…”
Section: Resultsmentioning
confidence: 99%